C.S. Lewis letters to children - Lewis, C. S. (Clive Staples), 1898-1963.; Dorsett, Lyle W.; Mead, Marjorie Lamp.; Gresham, Douglas H., 1945- (New York : Simon & Schuster, 1995)
A collection of letters from the English author of the Narnia books to a variety of children.
"A Touchstone book."
Includes bibliographical references (p. 115-120).
Keywords: Lewis, C. S. -- 1898-1963; Authors, English -- 20th century -- Correspondence; Children -- Correspondence; Fantasy fiction -- Authorship; Children's stories -- Authorship; Lewis, C. S. -- 1898-1963; Authors, English -- Correspondence